The amount of solar energy made available for the production of a sabiá (Mimosa caesalpinaefolia Benth.) seed has a determinating effect on its becoming dormant - De Carvalho, N. Moreira [UNESP]; Ursulino Alves, E. [UNESP]; Gonçalves, E. P. [UNESP] (My University, 2002)
The amount of solar energy made available for the production of a sabiá seed varied as a function of the time of the year, the face of the plant in which, the position in the plant on which and the position in the pod in which it was produced. Variation in solar energy availability as a consequence of the time of the year was a direct consequence of latitude. At 21° 5'22 S the highest amounts of Global Solar Radiation (GSR) reaching the site where the experiment was conducted took place during the months from November through February. During these months there were no marked differences between any two of the amounts of GSR reaching faces North (N), South (S), West (W) East (E). From February through November (period during which the sabiá plants of this study flowered and the resulting seeds matured and were harvested) the total GSR's were the lowest and marked differences were found between faces N and S, with face N receiving much more GSR than face S. During that period, faces W and E received practically the same amount of GSR and it was much less than that received by face N and much more than the one received by face S. The amount of biological energy made available for the development of a seed seemed also to vary according to a dry matter partitioning strategy by the plant -the central third of the plant seemed to be the one receiving the highest amounts of energy, followed either by the upper or the lower third of the plant- it was not very clear which third of the plant immediately followed the central one. The partitioning of biological energy at the pod level also seemed to follow a strategy by which the central seeds would be the ones to receive more, followed by the proximal seeds and these by the distal ones. This availability of energy seemed to have a direct effect on seed size, weight and on the percentage of seeds which showed a degree of dormancy deep enough to prevent their germinating under the conditions of a standard germination test. The implications of these results for the improvement of methods for the overcoming of dormancy of sabiá seeds are discussed.